First report on the occurrence of Avicennia marina (Forssk.) Vierh. (Acanthaceae) in the Nicobar archipelago (Ocean and Coastal Research, 2022)
The 2004 Sumatra-Andaman earthquake (9.2 Mw) and tsunami that followed it resulted in uplift and subsidence across the Andaman and Nicobar archipelago. This unusual natural event severely affected the mangrove and coastal ecosystems across the Andaman and Nicobar Islands. The tsunami and land drowning of 1.1-2.85 m resulted in considerable loss of mangrove habitats in the Nicobar archipelago. Meanwhile, the land drowning also created new intertidal habitats in the earlier terrestrial zones that are now providing suitable conditions for the colonization of mangroves. During the long-term monitoring of mangrove colonization in these new inter-tidal zones, we identified the first occurrence of the Avicennia marina (Forssk.) Vierh. in the Nicobar archipelago. The distribution of A. marina and the characteristics of its colonizing sites are discussed herein.